Pengembangan Aplikasi Monitoring Perkembangan Siswa Yayasan Pembinaan Anak Cacat (YPAC) Malang berbasis Web - Riza Setiawan; Fajar Pradana; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Disability Development Foundation (YPAC) Malang is a social organization that provides integrated rehabilitation services for children with disabilities and special needs. One of the most important parts of YPAC Malang is students and their grades. In one school there are hundreds of students and each has a different value. In addition, the problem faced is that parents do not know about child development information every month, parents only know the child's development from the report card grades distributed each semester. This application is designed using Object Oriented Analysis and Design (OOAD) and implemented with the php language with the help of the Laravel 6.2 and Bootstrap framework 4. Application testing uses white box testing and black box testing with the results of this application in accordance with the functional requirements that have been specified. The results of compability testing in this application have successfully shown that the application runs successfully in various types of common browsers such as Google Chrome, Mozilla Firefox, or Microsoft Edge.